PELATIHAN PEMBUATAN SABUN CAIR DAN SHAMPOO PENCUCI MOBIL - Denny Akbar Tanjung (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2017)
The training activities of making liquid soap and car wash shampoos are intended to provide knowledge of the procedure of making liquid soap and shampoo car wash simply and can be done at home. Liquid soap that serves as a remover of dirt and fat on the plate is one of the needs in the household whose role cannot be replaced with other objects. By making your own liquid soap means saving the household budget for soap items by 50%. However, if it can mass produce means to create business opportunities. Our hope of this community service activity is that students can work by producing quality liquid soap that meets the standards for both personal and commercial consumption. In this community service there are 3 sessions conducted, the first is education about the definition of soap, soap origin, soap type and function. The second session is training on making liquid soap and car wash shampoos. In the manufacture of liquid soap the basic ingredients used are SLS, Texapon and Salt. Subsequently, added additives such as fragrances, preservatives, thickeners and dyes. After that the last session is to calculate the production cost to make liquid soap. Because using simple tools is expected students can try it at home.